2019
DOI: 10.1080/15213269.2019.1679647
|View full text |Cite
|
Sign up to set email alerts
|

The effects of social information on the enjoyment of online videos: An eye tracking study on the role of attention

Abstract: Recent experiments showed that the valence of user comments (i.e., social information) presented alongside online videos can alter viewers' enjoyment of videos. However, it is unclear how much attention video viewers pay to social information and whether the effects found in previous studies occur if participants are not forced to view the social information. Therefore, this study investigated how the valence of social information presented alongside online videos affects viewers' enjoyment when viewers are fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
(47 reference statements)
2
9
0
Order By: Relevance
“…Consequently, when significant interactions were followed up using simple effects analysis a Bonferroni correction was used to reduce the chances of obtaining false-positive results (type I errors). This is consistent with the analytical approach used in similar research (Landrum et al, 2019;Möller et al, 2019). Trends are reported when effect sizes, calculated using partial eta squared, are medium to large.…”
Section: Analytic Approachsupporting
confidence: 86%
“…Consequently, when significant interactions were followed up using simple effects analysis a Bonferroni correction was used to reduce the chances of obtaining false-positive results (type I errors). This is consistent with the analytical approach used in similar research (Landrum et al, 2019;Möller et al, 2019). Trends are reported when effect sizes, calculated using partial eta squared, are medium to large.…”
Section: Analytic Approachsupporting
confidence: 86%
“…Thus, it seems that especially a negative valence of comments can diminish viewers' experiences of videos as a source of fun, appreciation and learning at the same time. This suggests that a negativity bias occurs in the processing of user comments as was previously, for example, also found in the context of news consumption (Damstra and Boukes, 2021), entertainment (Möller et al, 2021), or human responses in general (Ito et al, 1998).…”
Section: Discussionsupporting
confidence: 69%
“…Many people watch political satire videos via social media (Baym and Shah, 2011; Yang and Jiang, 2015), which embed these videos in a social context consisting of user comments and (dis)likes. Extant research investigated the potential consequences of this social environment; these studies found that user comments more so than statistics about likes or dislikes affected viewers when they watch online videos (Möller et al, 2021; Winter et al, 2015). However, the effects of user comments on viewers’ experiences of political satire videos, in particular, are still unknown.…”
Section: Mixed Value: Satire As a Source Of Entertainment And Informa...mentioning
confidence: 99%
See 2 more Smart Citations